2021
DOI: 10.1177/09544089211034029
|View full text |Cite
|
Sign up to set email alerts
|

Simulation and experimental investigation of multi-walled carbon nanotubes/aluminum composite fabrication using friction stir processing

Abstract: Multi-walled carbon nanotube/aluminum composites are fabricated on Al–Si cast alloy employing friction stir processing. First, the microstructure of the stir zone, as well as the effect of process parameters on the size of silicon particles, is investigated. Then, the process is numerically simulated using a thermo-mechanically coupled three-dimensional finite element method model. Material flow, as the primary reason for the dispersion of reinforcing particles, is considered in the numerical model, and proper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(19 citation statements)
references
References 36 publications
0
17
0
2
Order By: Relevance
“…Akbari and Asadi (2021) fabricated the MWCNT/aluminum composites using friction stir processing. Results showed that the uniform particle distribution occurred while changing the tool rotation direction among the friction stir passes.…”
Section: Introductionmentioning
confidence: 99%
“…Akbari and Asadi (2021) fabricated the MWCNT/aluminum composites using friction stir processing. Results showed that the uniform particle distribution occurred while changing the tool rotation direction among the friction stir passes.…”
Section: Introductionmentioning
confidence: 99%
“…Friction stir processing (FSP) is another promising solid-state method that is able to produce MMCs. However, this method is primarily used to produce surface composites [5,6] and requires extensive process optimization and simulation to understand the effects of those parameters on the homogeneity of the composite [7] . Liquid-state methods usually involve different ways of introducing the reinforcement particles into the liquid melt [8] .…”
Section: Introductionmentioning
confidence: 99%
“…Multi-walled carbon nanotube/aluminum composites are produced by Akbari and Asadi. 19 It was shown that the wear resistance and hardness of the produced composites are considerably enhanced compared to the base alloy. Butola et al 20 fabricated AA7075-T6 reinforced by B 4 C using FSP by varying process parameters including tool rotational speed, tool pin profile and tool traverse speed.…”
Section: Introductionmentioning
confidence: 99%